2004
DOI: 10.1007/s00520-004-0682-6
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan, health-related quality of life and self-esteem: A randomized trial with breast cancer survivors

Abstract: In this pilot investigation, the TCC group exhibited improvements in HRQL and self-esteem from baseline to 6 and 12 weeks, while the support group exhibited declines. Randomized, controlled clinical trials with larger sample sizes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
3
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(173 citation statements)
references
References 33 publications
4
156
3
10
Order By: Relevance
“…Finally, 9 RCTs were selected for this systematic review where there were 3 RCTs published in Chinese (He et al, 2011;Qiang et al, 2011;Wang et al, 2012), and others were published in English (Mustian et al, 2004;Mustian et al, 2006;Rausch 2007;Mustian et al, 2008). In addition, five RCTs resulted from the same population or trial were included in our study (Mustian et al, 2004;Mustian et al, 2006;Mustian et al, 2008;Janelsins et al, 2011;Sprod et al, 2012). Among them, only the trial performed by Mustian (2006) together with the other four RCTs (Rausch 2007;He et al, 2011;Qiang et al, 2011;Wang et al, 2012) was included in the meta-analysis.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 9 RCTs were selected for this systematic review where there were 3 RCTs published in Chinese (He et al, 2011;Qiang et al, 2011;Wang et al, 2012), and others were published in English (Mustian et al, 2004;Mustian et al, 2006;Rausch 2007;Mustian et al, 2008). In addition, five RCTs resulted from the same population or trial were included in our study (Mustian et al, 2004;Mustian et al, 2006;Mustian et al, 2008;Janelsins et al, 2011;Sprod et al, 2012). Among them, only the trial performed by Mustian (2006) together with the other four RCTs (Rausch 2007;He et al, 2011;Qiang et al, 2011;Wang et al, 2012) was included in the meta-analysis.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Previous researches in BCS showed that TC improves functional capacity (Mustian et al, 2006), QoL (Mustian et al, 2008), and self-esteem (Mustian et al, 2004) and can regulate growth factors and binding proteins associated with weight gain and bone loss (Peppone et al, 2010;Janelsins et al, 2011). However, to our knowledge, these studies have a relatively small sample size with wide variation and convey mixed and inconclusive results.…”
Section: Introductionmentioning
confidence: 90%
“…These prior studies focused primarily on aerobic activity. Previous randomized exercise intervention studies specifically among breast cancer survivors have reported that physical exercise such as walking, 14 aerobic exercise, 8,9,17 Tai Chi, 29 and upper extremity exercise 30 had beneficial effects on QOL. For instance, the Rehabilitation Exercise for Health After Breast Cancer (REHAB) trial 9 assessed the effects of a 15-week aerobic exercise intervention on postmenopausal breast cancer survivors and the results showed beneficial effects on changes in happiness, self-esteem, fatigue, and several subcomponents of overall QOL.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that age has a depressant effect on self-esteem (Orth, Trzesniewski, & Robins, 2010) but an over-optimistic effect on the estimation of life expectancy because of the fear of death (Pew Research Center, 2008). Practicing Tai Chi among older adults could reduce this depressant effect of the age on the self-esteem (M. S. Lee, Choi, & Ernst, 2010;Mustian et al, 2004;Wang et al, 2010), could reduce the levels of stress (Wang et al, 2010), and might even provide a more realistic perceived life expectancy. To perceive the beneficial effects of Tai Chi on health, a minimum practice of 3 hr a week during 3 months is required (Hong, 2008).…”
Section: Research-article2014mentioning
confidence: 99%